High-Sensitivity Cardiac Troponin T Concentrations below the Limit of Detection to Exclude Acute Myocardial Infarction: A Prospective Evaluation. (6th January 2020) - Body, Richard; Burrows, Gillian; Carley, Simon; Cullen, Louise; Than, Martin; Jaffe, Allan S; Lewis, Philip S
Abstract: BACKGROUND: Initial reports suggest that concentrations of high-sensitivity cardiac troponin T (hs-cTnT) (Roche Diagnostics Elecsys ® ) below the limit of blank (LoB) (3 ng/L) or limit of detection (LoD) (5 ng/L) of the assay have almost 100% negative predictive value (NPV) for acute myocardial infarction (AMI), particularly among patients without electrocardiograph (ECG) evidence of ischemia. We aimed to prospectively validate those findings. METHODS: We included adults presenting to the emergency department with suspected cardiac chest pain. Standard troponin T (cTnT) and hs-cTnT (both Roche Elecsys) were tested in samples drawn on arrival. The primary outcome was AMI, adjudicated by 2 investigators on the basis of clinical data and ≥12-h cTnT testing. We also evaluated diagnostic performance when AMI was readjudicated on the basis of hs-cTnT (≥12-h) concentrations. RESULTS: Of 463 patients included, 79 (17.1%) had AMI. Twenty-four patients (5.2%) had hs-cTnT concentrations below the LoB, although none had AMI. Ninety-six patients (20.7%) had hs-cTnT concentrations below the LoD, 1 of whom had AMI. Thus, diagnostic sensitivity was 98.7% (95% CI 87.5%–98.6%) and NPV was 99.0% (95% CI 94.3%–100.0%). Of the 17.3% (n = 80) patients with hs-cTnT below the LoD and no ECG ischemia, none had AMI. Thus, diagnostic sensitivity was 100.0% (95% CI 95.4%–100.0%) and NPV was 100.0% (95% CI 95.5%–100.0%). Sensitivity and NPV were maintained when AMI was readjudicated on the basis of hs-cTnT. CONCLUSIONS: Our findings confirm that patients with nonischemic ECG and undetectable hs-cTnT at presentation have a very low probability of AMI, although the proportion of patients affected was smaller than in previous research.